La caida del mapajo : pueblo indígena Yuracare (CEFREC-CAIB, 2012)
Jazmina Antezana, indigenous Yuracaré from the La Frontera community located on the banks of the Chimoré River, tells us about the customs and experiences of her people, she lives in the city but always returns to her land to listen to the teaching of her parents, about the importance to take care of our forests and nature, especially the care of a tree that is respected by the people that is the Mapajo. "They say that the owner has a raccoon and at night a door opens and inside it has a lot of riches especially musical instruments and if you go in and take out one of them you become expert and when you cut a raccoon a bad thing fell on your family" .--